The Challenges of Marketing Communication in the Context of Outsourcing and Virtualization of Marketing - Hajduk , Grzegorz (Studia Oeconomica Posnaniensia, 2017)
The article addresses the current limitations of using integrated marketing communications. The article also discusses the impact of consumers on the effectiveness of brand building, which in turn could result in the loss of control over the process. The phenomenon of outsourcing and marketing virtualization has been characterized by changing the rules of communication between companies and their market environment. Described phenomena and dependencies were identified by the author in the course of research and the author conducted on his own during observation of the companies’ marketing activity.